PENGARUH KONSENTRASI NACL TERHADAP ELEKTROOSMOSIS KAOLINIT - Semuel Erari (NIM : 20297501), Ishak
Abstract : Electroosmosis test on kaolinite are conducted with using four concentration levels of NaCl. The concentrations are 0 M (destilated water); 0.001 M; 0.01 M; and 0.1 M. Results of electroosmosis represent that electrokinetic potential, flow rate, total dehidrated fluid, coefficient of electroosmotic permeability increase with increasing concentration of NaCL. All position of shear plane are out of the double layer thickness. This position is closer to the surface of particle with higher concentration of NaCl. Transport efficiency increase up to 0.01 M, and lowest transport efficiency is 0.1 M NaCl.